2019
DOI: 10.3389/fpls.2019.01000
|View full text |Cite
|
Sign up to set email alerts
|

A Toolkit for High Resolution Imaging of Cell Division and Phytohormone Signaling in Legume Roots and Root Nodules

Abstract: Legume plants benefit from a nitrogen-fixing symbiosis in association with rhizobia hosted in specialized root nodules. Formation of root nodules is initiated by de novo organogenesis and coordinated infection of these developing lateral root organs by rhizobia. Both bacterial infection and nodule organogenesis involve cell cycle activation and regulation by auxin and cytokinin is tightly integrated in the process. To characterize the hormone dynamics and cell division patterns with cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The sterilized seeds were germinated on petri dishes lined with moist filter paper and transferred to magenta boxes containing moist vermiculite. Plants were grown at 21 °C with a photoperiod of 16/8 h. In parallel, plasmids LjUbi:YFP 16 and LjUbi:VC1 were conjugated into Agrobacterium rhizogenes GV3101 using triparental mating 17 . We then infected the in-vitro- grown plants with the transformed A. rhizogenes using a protocol adapted from Kereszt et al 18 .…”
Section: Methodsmentioning
confidence: 99%
“…The sterilized seeds were germinated on petri dishes lined with moist filter paper and transferred to magenta boxes containing moist vermiculite. Plants were grown at 21 °C with a photoperiod of 16/8 h. In parallel, plasmids LjUbi:YFP 16 and LjUbi:VC1 were conjugated into Agrobacterium rhizogenes GV3101 using triparental mating 17 . We then infected the in-vitro- grown plants with the transformed A. rhizogenes using a protocol adapted from Kereszt et al 18 .…”
Section: Methodsmentioning
confidence: 99%
“…Gravitropic stimulation of roots, which results in asymmetric auxin distribution, is also sufficient to alter nodule positioning in L . japonicus ( Nadzieja et al., 2019 ), and application of auxin import inhibitors before rhizobia infection reduced the number of nodules in M . truncatula ( Roy et al., 2017 ).…”
Section: Auxinmentioning
confidence: 99%
“…japonicus and M . truncatula demonstrated that auxin signaling starts to emerge in cell layers underneath infected root hairs and is strongest in the cortex and pericycle of young nodules ( Pacios-Bras et al., 2003 ; Suzaki et al., 2012 ; Breakspear et al., 2014 ) and in the vasculature and apex of mature nodules ( Takanashi et al., 2011 ; Suzaki et al., 2012 ; Guan et al., 2013 ; Breakspear et al., 2014 ; Franssen et al., 2015 ; Nadzieja et al., 2019 ). These observations support a requirement for auxin signaling in both infection and nodule organogenesis and may relate to the requirement for cell-cycle initiation and progression that occurs in both these processes.…”
Section: Auxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional transcription factors (NSP1, NSP2, ERN1 and NIN) are then required for infection thread formation [23][24][25][26][27][28][29] involving a pectate lyase encoded by Npl, actin rearrangement by NAP1, PIR1, SCARN, ARPC1 and DREPP, an E3 ubiquitin ligase encoded by Cerberus, an atypical receptor kinase encoded by RinRK, a subunit of mediator complex encoded by Lan, and novel functions encoded by Rpg, Vapyrin and CBS [30][31][32][33][34][35][36][37][38][39][40] . The simultaneous development of nodule organs is mediated by NSP1, NSP2, ERN1, NIN and NF-Ys transcription factors 41,42 that together with localized changes in plant hormone homeostasis (cytokinin, auxin and jasmonic acid) regulate initiation of infection thread formation and cell divisions leading to nodule organogenesis [43][44][45][46] . In contrast, ethylene and abscisic acid suppress nodule formation [47][48][49] .…”
Section: Introductionmentioning
confidence: 99%